Rapid Visual Detection of Hepatitis C Virus Using Reverse Transcription Recombinase-Aided Amplification–Lateral Flow Dipstick - Wang, Haili; Zhang, Yuhang; Zhou, Jingming; Li, Ming; Chen, Yumei; Liu, Yankai; Liu, Hongliang; Ding, Peiyang; Liang, Chao; Zhu, Xifang; Zhang, Ying; Xin, Cheng; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Hepatitis C virus (HCV) infection is a global public health threat. Reaching the World Health Organization (WHO) objective for eliminating viral hepatitis by 2030 will require precise disease diagnosis. While immunoassays and qPCR play a significant role in detecting HCV, rapid and accurate point-of-care testing (POCT) is important for pathogen identification. This study establishes a reverse transcription recombinase aided amplification-lateral flow dipstick (RT-RAA-LFD) assay to detect HCV. The intact workflow was completed within 30 min and the detection limit for synthesized C/E1 plasmid gene-containing plasmid was 10 copies/μL. In addition, the test showed good specificity, with no cross-reactivity observed for hepatitis A virus (HAV), hepatitis B virus (HBV), HIV, syphilis, and human papillomavirus virus (HPV). Using extracted RNAs from 46 anti-HCV antibody-positive samples, RT-RAA-LFD showed 100% positive and negative concordance rates with qPCR. In summary, the RT-RAA-LFD assay established in this study is suitable for rapid clinical detection of HCV at the community level and in remote areas.